2022
DOI: 10.3390/ma15249014
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cold Sprayed Titanium and Titanium Alloy Coatings after Laser Surface Treatment

Abstract: Additive manufacturing (AM) has seen remarkable development in recent years due to relatively high efficiency of the process. Cold spraying (CS) is a particular method of AM, in which titanium and titanium alloy powders are used. CS is a very competitive technology enabling the deposition of coatings, repairing machine parts, and manufacturing new components. For specific applications, the surface of cold-sprayed materials may require further processing. This paper reports an attempt to employ laser surface tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…Наразі відомі позитивні результати з формування гомогенних покриттів на титанових сплавах з використанням установок ХГН високого тиску [4]. В таких установках в якості робочого газу використовується гелій під високим тиском -до 50 МПа, а робочі температури сягають 900 °С.…”
Section: вступunclassified
See 1 more Smart Citation
“…Наразі відомі позитивні результати з формування гомогенних покриттів на титанових сплавах з використанням установок ХГН високого тиску [4]. В таких установках в якості робочого газу використовується гелій під високим тиском -до 50 МПа, а робочі температури сягають 900 °С.…”
Section: вступunclassified
“…В роботі проведено експериментальне дослідження впливу температури газу на вході в сопло на адгезійну міцність покриттів, отриманих з порошкової суміші Ni+Zn+Al2O3, холодним газодинамічним напилюванням низького тиску. За результатами встановлено, що зі збільшенням температури газу, яке реалізується на використаному обладнані шляхом встановлення температурного режиму (3)(4)(5), адгезійна міцність покриттів зростає в середньому зростає з 9,5 МПа до 28,7 МПа. Мінімальне значення адгезійної міцності покриттів, що наносяться холодним газодинамічним напилюванням, відповідно до промислових рекомендацій, становить 15 МПа.…”
Section: висновкиunclassified
“…It is worth noting that the Laser-Assisted Cold Spray (LACS) method [18], developed using a combination of these techniques, is currently being developed alongside traditional laser-based additive manufacturing methods [19]. In [20][21][22][23][24][25][26], the prospects of laser post-processing for modifying the structure and properties of metalbased cold-sprayed coatings were reported. Sova et al [20] showed that laser remelting of a 316L coating can significantly reduce its porosity and improve its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Stutzman et al [23] were able to optimize laser processing parameters to prevent stress corrosion cracking in an alloy 600 coating. Zybala et al [24] reported both a growth in microhardness and surface hydrophilicity and an increase in residual stresses of titanium and Ti64 alloy coatings after laser treatment. Laser processing is also used to produce alloys from coatings fabricated using metal powder mixtures [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have also attempted to improve the overall performance of titanium and titanium alloy coatings by auxiliary means, such as solid solution treatment, heat treatment, substrate preheating, hot isostatic pressing treatment, etc. The significant change in the surface morphology and the increase in the residual stress level of the coating depend on the interaction time of the laser beam [29]. The bonding strength of the cold sprayed coating can be improved by solid solution and aging treatment [30].…”
Section: Introductionmentioning
confidence: 99%